Molecular crosstalk between tumour and brain parenchyma instructs histopathological features in glioblastoma - Bougnaud, Sébastien; Golebiewska, Anna; Oudin, Anaïs; Keunen, Olivier; Harter, Patrick Nikolaus; Mäder, Lisa; Azuaje, Francisco; Fritah, Sabrina; Stieber, Daniel; Kaoma, Tony; Vallar, Laurent; Brons, Nicolaas H. C.; et al. (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.7454 Sébastien Bougnaud, Anna Golebiewska, Anaïs Oudin, Olivier Keunen, Patrick N. Harter, Lisa Mäder, Francisco Azuaje, Sabrina Fritah, Daniel Stieber, Tony...